PENGUATAN KOMPETENSI GURU SEKOLAH DASAR DALAM GAME BASED LEARNING MELALUI PROGRAM PKM KKN BERBASIS KAMPUS - Arifin Maksum; Arita Marini; Juhana Sakmal; Wahyu Sri Ambar Arum; Dinda Putri Nabila; Febyarni Resvatina; Chika Aurellia Maharani; Shabrina Ramadhiani; Shifaa Qurratu Aini; Leola Dewiyani (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Community Service Program (PkM) through the Community Service Learning Program (KKN) at SDN Tanah Tinggi 05, Central Jakarta, was conducted to enhance elementary school teachers’ competencies in implementing integrated Game-Based Learning (GBL). This approach was designed to create a more interactive, enjoyable, and meaningful learning environment, thereby increasing student engagement and learning motivation. Furthermore, GBL supports the development of essential 21st-century skills, including critical thinking, problem-solving, communication, and collaboration. The program was implemented through training sessions, mentoring activities, and hands-on practice in designing, implementing, and evaluating game-based learning strategies tailored to students’ developmental characteristics. It involved collaboration among lecturers, university students, and teachers within an integrated KKN framework aimed at promoting student-centered learning practices. The results indicated significant improvements in teachers’ pedagogical competence, creativity, and digital literacy, particularly in developing innovative learning media and instructional strategies based on educational games. Teachers became more capable of creating engaging and effective classroom experiences, which positively influenced student participation in learning activities. In addition to benefiting the school community, the program also provided valuable service-learning experiences for university students. Overall, the program contributed to improving the quality of elementary education while strengthening sustainable partnerships between higher education institutions and schools.